Naskah Naskah Kuno Di Provinsi Jambi Sebagai Sumber Arkeologi - Yusdi Andra (Jurnal Ilmiah Dikdaya, 2019)
Searching for the Malay kingdom which is related to the  manuscripts originated  mostly from Chinese records which is evidenced   that  Jambi Malay  ever triumphed and connected to Tiongkok in the past. Other data that can support the manuscripts of the ancient of Jambi Malay in classical times, in Jambi Malay land the government system was carried out from generation to generation in a royal family which was respected by the wider community. Almost all the Malay manuscripts were written in Jawi letters (the Malay letters = the Bald Arabic letters), could be predicted that the writing of Malay manuscripts were started around 14th century. Meanwhile the previous Malay manuscripts were written in Jawi letters, and were suspected before Islam came to Indonesia. By finding Tanjung Tanah manuscript proved that Malay people had pre-Islamic manuscript tradition. In that era, the manuscripts  were also written on the bark, reed, palm leaf, and horn. Generally, the manuscripts contain the local chronics, tradition, religion, correspondences, king’s documents,  languages and arts, tasauf / philosophy, education and even medicines. If we see from the writing, it is clear that the substitution of the writing that from oral tradition to written tradition. Jambi  province has many interesting goods, related to the ancient manuscripts which were  only a small portions that had been recorded and saved in the museum. While the most part portions still saved by the people. The result of the research showed the manuscript elements I; (1) Kerinci was under controlled by Jambi kingdom at that time, (2) Islam could not be accepted generally and Syari’a law in Kerinci land did not work well. Manuscript element II (1)  the emptiness position as a king in Jambi, the coming of Princess Selaras Pinang Masak  became a king in Ujung Jabung, the story of Ahmad Salim from  Sultan Turki’s descendent whose ship broke up and stranded in Berhala island, and the story of Ahmad Salim’s wedding titled Datuk Paduko Berhalo with Princess Selaras Pinang Masak was the beginning of the growth of Islam in Jambi. Manuscript element III (1) Orang Kayo Hitam was the youngest child of Princess Selaras Pinang Masak  with Datuk Paduko Berhalo, he graced much the story of Jambi from the beginning of Islam era that grew in Jambi. When he was adult, he saw the suffering of his people collecting funds to be offered to Mataram kingdom as a tribute. In this case, Orang Kayo Hitam did not agree what his people did, (2) Orang Kayo Hitam wished to be killed, but the plan of  King Mataram had been known by Orang Kayo Hitam, so he went alone to Java island to see the situation and would take back the Keris itself from King Mataram’s  hand. He disguised himself as he arrived in Java island and after learning its condition, with all of his ingenuities, Orang Kayo Hitam could know the place of where the Keris made. He killed the blacksmith and took that Keris, (3) King Mataram asked for peace, as a sign of the friendship of Orang Kayo Hitam whom marrried with one of his princess that is Ratumas Pemalang. Orang Kayo Hitam brought along that Keris in his hand, that was also announced that Keris named Keris Siginjai. Manuscript element IV; (1) Orang Kayo Hitam in his married with Ratumas Pemalang had four children, they were Penambahan Ratu Kapas, Penambahan Rengas Pandak, Penambahan Bawah Sawo, and Penambahan Kota Baru, (2) in Sahibul Hikayat / Sahibul Saga, they used Panambahan as their title, where the title was  usually used by the kingdom of Mataram. The use of the name was because there was a marriage relationship between Orang Kayo Hitam with Ratumas Pemalang, a daughter of King Mataram.